Answer:
--- True
--- False
Explanation:
Given
![f(x) = (x^2)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/au699fd56s196zsg09wfno4toi473qdgl7.png)
Solving (a): f(6) = f(-6)
First, we solve for f(6) by substituting 6 for x in
![f(x) = (x^2)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/au699fd56s196zsg09wfno4toi473qdgl7.png)
![f(6) = (6^2)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/os51dacud4yjjsx4ytxh22fixlujyo3nau.png)
![f(6) = (36)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/a9pj03rlhmffe5t3c6uwgp6zj4vv4fozm2.png)
![f(6) = 12 - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/m2ab9g5z7zihlkydk7pccrktpv025efvqp.png)
![f(6) = 10](https://img.qammunity.org/2021/formulas/mathematics/high-school/c0hwgbq5ya0yefdmceock2sw0lrqbi0mel.png)
Next, we solve for f(-6) by substituting -6 for x in
![f(x) = (x^2)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/au699fd56s196zsg09wfno4toi473qdgl7.png)
![f(-6) = (-6^2)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/9xu0vjkf2087ry6l9sgnx5qywxsrjwfhot.png)
![f(-6) = (36)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/1505k3xesu3qhy470egbte4wh9nqarqs97.png)
![f(-6) = 12 - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/oe7t55lrricjgwu0mumuc21htp65ss7ned.png)
![f(-6) = 10](https://img.qammunity.org/2021/formulas/mathematics/high-school/umog1s7nrksh5zltr8jstn4z2i1gmf5mut.png)
We have that:
![f(6) = f(-6) = 10](https://img.qammunity.org/2021/formulas/mathematics/high-school/tp2umi88e0936spuuv13kqbubai14be07j.png)
Hence, the statement is true
Solving (b):
![f(6)=2 * f(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/s50biob2h9arrxxnu7nhngrpnszbhi451c.png)
We have that:
![f(6) = 10](https://img.qammunity.org/2021/formulas/mathematics/high-school/c0hwgbq5ya0yefdmceock2sw0lrqbi0mel.png)
Next, we solve for f(3) by substituting 3 for x in
![f(x) = (x^2)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/au699fd56s196zsg09wfno4toi473qdgl7.png)
![f(3) = (3^2)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/gce10ww83xr62hfbwsa522v5td5sz6l1qc.png)
![f(3) = (9)/(3) - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/ek1omhvcm1yilfe9g9cn68qg9avoun52y5.png)
![f(3) = 3 - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/oetpfgveqwszncogass4qz2ge2bwbj41np.png)
![f(3) = 1](https://img.qammunity.org/2021/formulas/mathematics/college/73m8lzmj4s1ko4v00v2mfbo03u1mpb32kr.png)
![2 * f(3) = 2 * 1](https://img.qammunity.org/2021/formulas/mathematics/high-school/69h5rvdnal3s49uoyg3d2lneisd1dpbn8z.png)
![2 * f(3) = 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/vje77sjuj29nrstahz35t5oyeffmsiqjur.png)
So:
![f(6)=2 * f(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/s50biob2h9arrxxnu7nhngrpnszbhi451c.png)
![10 \\eq 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/ewujoo5oye3tgjyz2umok4486fsuk6gmnm.png)
Hence, the statement is false